RESPONSE OF RICE TO NITROGENOUS FERTILIZER AND IRRADIATED SEWAGE SLUDGE (Biological Sciences - PJSIR, 2003)
4 2 A greenhouse pot experiment was conducted to study the effect of g-irradiated sewage sludge, applied alone or along with 15N-labelled ammonium sulphate (1.0 atom % 15N excess), on rice yield and N uptake. Six-kg portions of a clay loam were amended with sewage sludge to obtain N addition rates of 30, 60, 90 and 120 mg kg-1 soil. In other treatments, nitrogen was applied at 120 mg kg-1 as 15N-labelled ammonium sulphate or 120 mg kg-1 as 15NH -N + sludge-N in the ratios of 1:3, 1:1,or 3:1. All the treatments were given before transplanting rice. Three healthy seedlings (4-week old) of rice (Oryza sativa L., var. Bas-Pak) were transplanted pot-1 and the plants harvested at maturity. Application of sewage sludge caused a significant improvement in rice yield. Grain yield increased by 188% at sludge-N of 120 mg N kg-1. The yield benefit at similar rate of fertilizer N was 304%, the increase being more at higher rates of application. The increase in rice yield was dependent on uptake of N and sewage sludge significantly improved the availability of N to the plants. The additional plant N in sludge treated soil was partially attributable to enhanced mineralization of soil N and N fixation by free-living microorganisms. Application of inorganic N led to a significant increase in the availability of N to plants from soil organic matter and sewage sludge. Results of combined application suggested that substantial savings of fertilizer N can be made by using sewage sludge on rice fields.